Avaliação da sobreposição na semeadura do milho (Zea mays) utilizando uma semeadora de precisão - Dagios, Ravel Feron (2018)
The seeding process is one of the most important operations involved in the agricultural production system, and the quality of execution is a primordial factor for the success of the production. A common problem observed in this operation is the overlapping area of seeds among rows, because of field geometry, equipment width and adopted direction of seeding. Then, the general objective of the work was to evaluate maize productivity in two zones, with overlapping and without overlapping seeding. Aiming for it, it was sought to determine the area of overlapping seeding of the field, determining the number of plants per parcel, number of heads per parcel, total ear length, total ear diameter, number of ear rows, number of grains by ear, a thousand grain mass, and grain yield determination. The experiment was realized in an agricultural property located in the town of Tupanciretã-RS, in a 52.43 hectares area that has center pivot irrigation system, they used an agricultural tractor, equipped with standard auto pilot, with real-time kinematic (RTK) correction and a precision seeder, equipped with section disconnection in the seed dispenser, composed of 33 seeding lines. The experimental design was a randomized complete block design, in a 3x2 factorial form with four replications, composed of three corn hybrids in two management zones, without overlapping of seeding (SSS) and with overlapping of seeding (SSC). The results indicated that the total area of seeding overlap found in the field was 1.33 hectares, representing 2.54% of the area, where seeding occurred in the SSS treatment we reached in maize yield components total spike, a greater mass of a thousand grains and a larger amount of grains per spike, in contrast, where there was seeding occurred in the CSS treatment, presented a higher number of spikes per hectare. The yield of maize in the seeding areas in the CSS treatment, there was a higher number of spikes per hectare. The yield of maize in the seeding areas in the CSS treatment had a reduction of 27.7 sacks per hectare, representing a reduction of 11.36%, compared to the areas where seeding occurred in the SSS treatment.